2013
DOI: 10.1111/bjh.12316
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mitochondrial ferritin overexpression in normal and sideroblastic erythroid progenitors

Abstract: SummaryIn myelodysplastic syndromes with ring sideroblasts (MDS-RS), the iron deposited in the mitochondria of RS is present in the form of mitochondrial ferritin (FTMT), but it is unknown whether FTMT overexpression is the cause or the result of mitochondrial iron deposition. Lentivirus FTMTtransduced CD34+ bone marrow cells from seven healthy donors and CD34 + cells from 24 patients with MDS-RS were cultured according to a procedure that allowed the expansion of high numbers of erythroid progenitors. These c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 48 publications
(75 reference statements)
0
11
0
Order By: Relevance
“…Indeed, down regulation of increased mitoferrin expression reversed mitochondrial iron accumulation and ameliorated nervous system degeneration in a Drosophila model of Friedreich’s ataxia [30]. In general, the mitochondrial iron deposits in these syndromes contain oxidized iron [31], though iron is sometimes found in mitochondrial ferritin, an iron storage molecule [32] [33] [34]. Many myelodysplastic syndromes with sideroblastic anemia are attributable to mutations in the splicing factor SF3B1 .…”
Section: The Mystery Of Mitochondrial Iron Overload Diseases- How Is mentioning
confidence: 99%
“…Indeed, down regulation of increased mitoferrin expression reversed mitochondrial iron accumulation and ameliorated nervous system degeneration in a Drosophila model of Friedreich’s ataxia [30]. In general, the mitochondrial iron deposits in these syndromes contain oxidized iron [31], though iron is sometimes found in mitochondrial ferritin, an iron storage molecule [32] [33] [34]. Many myelodysplastic syndromes with sideroblastic anemia are attributable to mutations in the splicing factor SF3B1 .…”
Section: The Mystery Of Mitochondrial Iron Overload Diseases- How Is mentioning
confidence: 99%
“…Interestingly, recent studies have demonstrated that subjects carrying GATA2-sequence variations have high risk to develop MDS 40 , suggesting that this pathogenetic event might be responsible for the up-regulation of FtMt in the disorder, where we have shown to interfere with JAK2/STAT5 pathways leading to ineffective erythropoiesis 27 28 .…”
Section: Discussionmentioning
confidence: 87%
“…In particular, GATA2 is a key transcriptional regulator of haematopoiesis, highly expressed in pluripotent hematopoietic stem cells and in early erythroid cells 40 . In physiological condition FtMt is not detectable in erythroid cells, while it is demonstrated that in pathological condition, like myelodysplastic syndrome with ring sideroblasts (MDS-RARS), it is specifically highly expressed in the ring- syderoblasts 4 21 28 . Actually, it exists a close correlation between the presence of FtMt and the iron specific Prussian blue staining indicating that mitochondrial ferritin is the form of iron deposited in perinuclear mitochondria of ring sideroblasts 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it has been shown that overexpression of FtMt in K562 erythroid cells reduced Jak/STAT signaling and increased apoptosis [11]. In sideroblasts, erythroid progenitors FtMt expression occurred at the early stage of cell differentiation and was accompanied by reduced iron availability and increased apoptosis [12, 13]. Moreover, FtMt expressing cells transplanted in nude mice grew more slowly than their control counterpart [14].…”
Section: Introductionmentioning
confidence: 99%